Deflection and frequency monitoring of the Forth Road Bridge, Scotland, by GPS - Roberts, Gethin W.; Brown, Christopher J.; Meng, Xiaolin; Ogundipe, Oluropo; Atkins, Christopher; Colford, Barry (Thomas Telford, 2012)
The use of carrier phase kinematic GPS (global positioning system) has evolved into a reliable technique to measure both the three-dimensional magnitudes and frequencies of movements of structures. Techniques have been developed that tackle errors caused by multipath, tropospheric delay and issues relating to satellite geometry. GPS-derived movements compare well with data from both design predictions and structural models. Results from field trials carried out on the Forth Road Bridge are presented. This paper brings together key results that outline the procedure as well as a series of new data that indicate other potential applications. GPS data were collected continuously over a period of 46 h at a minimum rate of 10 Hz. During the trials wind speed, wind direction, relative humidity and temperature were also recorded. Frequently there was very heavy traffic flow, and at one point a special load (a 100-t lorry) passed over simultaneously to the heavy daytime flow of traffic. Data from a planned load trial during a brief bridge closure are reported and compared with the limited results available from a finite element model. Measured vibration frequencies are also computed from GPS data and compared with those given in the literature. In addition, results indicating the change in structural characteristics are also presented – in particular changes of mass associated with changes in traffic loading are observed. The results show the performance of GPS as it has developed in recent years, and that it can now reliably be used as a significant part of structural health monitoring schemes, giving both the magnitude of quasi-static deflections in known time periods and hence the frequency of dynamic movements of structures.